Pengembangan Aplikasi Manajemen Antrean Pesanan Menu Restoran dengan Memanfaatkan Teknologi Kode QR - Yahya Sahaja; Agi Putra Kharisma; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The problems happen in a restaurant for serving customers are too diverse. Many of restaurants in Malang are still just giving the menu list manually to the customers, that the restaurant should print the updated menu. Besides, ordering in a restaurant is still just using paper, that the customers should write the menu manually to order, and give it back to the restaurant waiters. The impact is that it can take too much time and costs more energy to the waiter as well as handling the restaurant menu ordering, even if there are so many customers should be served. Based on those problems, the writer wants to make an application that can handle restaurant food ordering queue management, hopefully this application could automate queue system in a restaurant. This application is built with following Agile methodology implementing Scrum framework, because the requirements are still developing within the application development. The result of this research was focused to solve the problems as well as simplify the queue management process and menu ordering in a restaurant. The researcher would also test the system with validation and usability test. The usability test was done for determining the usability level as the customers view point. For the result, validation testing states that the validations for every sprint is valid and usability testing states that the usability value for customers application got 82,25% score belonging in an B category with adjective rating excellent, whereas the application for restaurant operator got 96.25% belonging as an A category with adjective rating best imaginable.